Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Intervening (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2017-2019) - Dhian Andanarini Minar Savitri; Dian Kurniasari; Amos Mbiliyora (Jurnal Akuntansi dan Pajak, 2021)
ABSTRACT This study aims to analyze the factors that influence firm value with capital structure as a intervening variable in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019.This research is a causal research with ex post facto type. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sampling technique is purposive sampling, which is collecting samples with certain criteria as a benchmark for collection, so that a sample of 141 companies is obtained. Data collection techniques with the method of documentation that is analyzing the company's annual report. Data analysis techniques used to answer the research hypothesis are multiple regression which are operated through the SPSS program.The research shows that profitability and firm size has no effect on firm value, Profitability has a negative effect on capital structure, firm size has a positive effect on capital structure,capital structure has a negative effect on firm value, and capital structure has no proven to mediate the effect of profitability and firm size to firm value.